Catalytic cracking feedstock composition and properties investigation for the process digital twin development purpose; Химия и химическая технология в XXI веке; Т. 2 - Oreshina A. A. (Химия и химическая технология на иностранном языке (английский), 2021)
Заглавие с титульного экрана